A Wideband Waveguide Antenna with Nearly Equal E- and H-Plane Radiation Patterns - Mei Qing Qi; He-Xiu Xu; Hui Feng Ma; Mou Ping Jin; Wei Wang; Tie Jun Cui (International Journal of Antennas and Propagation)
A novel wideband waveguide antenna with excellent performance is proposed, which is composed of a coaxial-waveguide transition and an open-ended rectangular waveguide loaded with a pair of horizontal umbrella-shaped metallic brims. The brims perpendicular to two broad walls of the waveguide are constructed to modulate the antenna to radiate nearly identical E- and H-plane radiation patterns. A wideband impedance matching performance is achieved with a fractional bandwidth of 40% through the introduction of short-stepped ladders. The antenna has the advantages of simple structure, symmetric radiation pattern, low-cross polarization, moderate back lobe, and almost constant beamwidth.